Uncertainty and Risk-aversion in a Dynamic Oligopoly with Sticky Prices - Edilio Valentini; Paolo Vitale (Fondazione Eni Enrico Mattei (FEEM), 2019)
In this paper we present a dynamic discrete-time model that allows to investigate the impact of risk-aversion in an oligopoly characterized by a homogeneous non-storable good, sticky prices and uncertainty. Our model nests the classical dynamic oligopoly model with sticky prices by Fershtman and Kamien (Fershtman and Kamien, 1987), which can be viewed as the continuous-time limit of our model with no uncertainty and no risk-aversion. Focusing on the continuous-time limit of the infinite horizon formulation we show that the optimal production strategy and the consequent equilibrium price are, respectively, directly and inversely related to the degrees of uncertainty and risk-aversion. However, the effect of uncertainty and risk-aversion crucially depends on price stickiness since, when prices can adjust instantaneously, the steady state equilibrium in our model with uncertainty and risk aversion collapses to Fershtman and Kamien's analogue.
Keywords: D8; D81; L13; 330; Uncertainty; Risk-aversion; Dynamic Oligopoly